PENGANTAR MODEL PEMBELAJARAN BLENDED LEARNING MENGGUNAKAN FACEBOOK DI SMAN 3 LENGAYANG - Ena Suma Indrawati; Yeni Nurpatri; Zaturrahmi; Desy Eka Muliani; Ilham Adi Putra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The development of information technology has brought significant changes in the world of education. The blended learning model is an innovative solution that combines face-to-face learning with digital technology. This study aims to introduce the use of the Facebook social media platform as a learning tool at SMAN 3 Lengayang. This service program is designed to increase the effectiveness of the teaching and learning process, encourage active interaction between teachers and students, and improve student participation in the learning process. The implementation method involves several stages, namely initial surveys, teacher and student training, program implementation, and program effectiveness evaluation. The survey results showed a significant increase in several aspects, including student active participation which increased from 45% to 85%, the frequency of teacher-student interaction increased from 2 to 5 times per week, and teacher satisfaction which increased by 80%. This program also helps increase student learning independence from 40% to 75%. The challenges faced include limited internet access, low student motivation, and lack of technological devices. Solution efforts carried out include providing internet access in the school environment, lending devices to students, and providing incentives to increase online learning motivation